Healthcare providers’ perspectives of barriers and facilitators to highly active antiretroviral therapy adherence among HIV-positive women in Southern Ethiopia: A qualitative study - Alemayehu Abebe Demissie; Elsie Janse van Rensburg (PLoS ONE, 2025)
Background Following a strict regimen of highly active antiretroviral therapy (HAART) is the fundamental factor in achieving successful treatment outcomes for HIV/AIDS. Poor adherence to HAART not only amplifies the risk of HIV transmission but also leads to deteriorating health, treatment failures, and a rise in drug-resistant HIV strains, ultimately contributing to increased morbidity and mortality rates. Therefore, the objective of the study is to explore and describe the perceptions of healthcare providers about HAART adherence of women in Southern Ethiopia who are HIV positive. Methods Focus group discussions (FGDs) were used among 27 healthcare providers (HCPs) (13 medical doctors and 14 nurses) to determine the extent of HAART adherence among HIV-positive women in Southern Ethiopia. The interviews were conducted in the local Amharic language and were audio recorded with permission from the participants. The FGDs were transcribed verbatim, coded for themes, categories and subcategories, and analyzed using thematic data analysis. Results The findings of the study reflected two themes: barriers to and facilitators of HAART medication adherence among HIV-positive women. These included patient-related factors, treatment-related factors, psychosocial-related factors, family- and community-related factors, and healthcare service-related factors. The following were identified as barriers to HAART adherence: Stigma and discrimination, gender roles, lack of money for food and transport, depression, busy schedule, forgetting of doses, religion, drug side-effects, pills burden, and size, dosage frequency, long waiting time, and unavailability of services at weekends. However, perceived benefits of HAART, family responsibility, reminders, family support, dosage formulation, experiencing improved health on HAART, relationship with healthcare providers, adherence counselling and education, and adherence supporting peer groups were identified as facilitators of HAART adherence. Conclusions Adherence to HAART medication is a major challenge among HIV-positive women in Southern Ethiopia. Therefore, tailored strategies to enhance HAART medication adherence should be targeted to address the barriers identified in the study.